A Challenge of Nutritional Education and Social Innovation to Improve Adolescent Girls' Eating Habits (2024)
ABSTRACT: Introduction: Nutritional education that promotes empowerment in food choices contributes to improving food consumption and dietary practices among adolescent girls. Objective: To develop a nutritional education and social innovation challenge to promote healthy and conscious eating habits among adolescent girls in Medellin. Methods: We designed an educational intervention based on a flexible learning pedagogical model developed by the International Center for Education and Human Development Foundation (known in Spanish as CINDE). This model has three levels of training (theoretical, practical, and communication). Educational sessions were tailored to the nutritional needs and risks previously identified among adolescent participants and encouraged their empowerment in making dietary and nutritional decisions. Each session included five stages: memory, game, reflection, practice, and challenge. Educational materials were created with adolescent participation. Training in innovation and entrepreneurship was provided to develop productive projects addressing the identified issues; the three best projects received funding and promotion in local markets. Results: The nutritional education program, named CERES School, included six educational sessions on the following themes: Presentation of the characteristics of adolescents’ food consumption; the body as a territory and healthy habits; key aspects of healthy eating; fruits and vegetables vs. ultra-processed foods; legumes and vegetable blends; dairy products and derivatives. The adolescents developed the following productive projects: healthy beverages, healthy breakfasts with available foods, consumption of local fruits and vegetables, recipes with vegetable protein, creation of healthy sauces and dressings, strategies to improve body perception, social media for disseminating nutrition content, physical activity for health. Educational materials created included: a comic about adolescents’ food consumption, a recipe book with healthy preparations, and a workbook for recording information, completing activities, and evaluating progress. Given the program’s success, its reach was maximized with the design and implementation of a digital course that replicated the in-person educational sessions, validated and adjusted based on participant feedback. Conclusions: Active participation and involvement of adolescent girls in the educational and social innovation process favored the sustainability and reach of the intervention. Conflicts of Interest: none